2014
DOI: 10.1111/imj.12334
|View full text |Cite
|
Sign up to set email alerts
|

Quality of care factors associated with unplanned readmissions of older medical patients: a case–control study

Abstract: Quality of care factors are more common among readmitted than among non-readmitted older patients suggesting potential for remedial strategies. Such strategies may still have limited effects as older, frail patients with advanced diseases and multimorbidity will likely retain a high propensity for readmission despite optimal care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
61
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(61 citation statements)
references
References 55 publications
(119 reference statements)
0
61
0
Order By: Relevance
“…These findings suggest that an involved inpatient medical and psychosocial assessment, including a focus on the transition of care and adherence to ART, may impact readmissions in this population. Some prior studies have identified similar quality issues during the inpatient stay as contributing to readmissions, 45,46 whereas others found that preventable causes of readmission were present during the index stay, discharge process and follow-up care. 32 Our study has several limitations.…”
Section: Discussionmentioning
confidence: 98%
“…These findings suggest that an involved inpatient medical and psychosocial assessment, including a focus on the transition of care and adherence to ART, may impact readmissions in this population. Some prior studies have identified similar quality issues during the inpatient stay as contributing to readmissions, 45,46 whereas others found that preventable causes of readmission were present during the index stay, discharge process and follow-up care. 32 Our study has several limitations.…”
Section: Discussionmentioning
confidence: 98%
“…In Australian populations, multimorbidity increases admissions, readmissions and ambulatory‐care‐sensitive admissions . There is scant literature on the role multimorbidity may play in unplanned admissions among PWH in Australia.…”
Section: Introductionmentioning
confidence: 99%
“…Patient characteristics such as age, main diagnosis, co-morbidities, and race have been studied and shown to be well-known risk factors [6789]. Patients who receive inappropriate or inadequate medical assessment and treatment are more likely to be readmitted, indicating not only are patient characteristics but quality of care is associated with readmission [10]. But, how other clinical factors impact readmission has been elusive and the results vary based on specific medical indicators and clinical conditions [1112].…”
Section: Introductionmentioning
confidence: 99%